3D and Inkjet Printing by Colored Mie-Resonant Silicon Nanoparticles Produced by Laser Ablation in Liquid - Lev Logunov; Aleksandr Ulesov; Vladislava Khramenkova; Xiuzhen Liu; Aleksandr A. Kuchmizhak; Alexander Vinogradov; Sergey Makarov (Nanomaterials, 2023)
Optically resonant silicon nanoparticles have emerged as a prospective platform for the structural coloration of surfaces because of their strong and spectrally selective light scattering. In this work, we developed colorful inks based on polymer mixed with monodisperse Mie-resonant silicon nanoparticles for 3D and inkjet printing. We applied a laser ablation method in a flow cell for the mass production of silicon nanoparticles in water and separated the resulting nanoparticles with different sizes by density-gradient centrifugation. Mixing the colorful nanoparticles with the polymer allows for the printing of 3D objects with various shapes and colors, which are rigid against environmental conditions.